The role of race, gender, and poverty on length of pretrial jail stays: A multi-site analysis - Ouellette, Heather M. (Criminology & public policy, 2025)
Research Summary The average length of jail stays is increasing despite national efforts to reduce these populations. The current study examines variations in lengths of stay, differentiating between short and long pretrial stays. Using data from two large jails in metropolitan jurisdictions, we take an intersectional perspective and model potential differences among race, gender, and residing in a high-poverty area. In both locations, we find that Black men are the most likely to have long lengths of stay, but that length of stay varies depending on the intersection of gender, race, and neighborhood poverty. Policy Implications: The human costs of pretrial detention are paid unequally by different groups of people. Given the downstream costs of pretrial detention, this work suggests that focusing policy efforts on the barriers to release among people of color, particularly Black men, would be fruitful. There is evidence that bail reform can reduce some barriers to release without increases in crime. Further, attending to obstacles to case processing could lead to pretrial system reform. This work also highlights another area of the criminal legal system where Black males, compared to their White counterparts, are disparately affected and denotes the continuing need for intersectional perspectives on reform.